Adsorption potential of poly(lactic acid)/polyaniline composites for the removal of indigo carmine dye from aqueous solutions - Isik, Birol; Ugraskan, Volkan (WILEY, 2025)
In this study, the adsorption performance of polyaniline-filled poly (lactic acid) on the removal of Indigo carmine dye was investigated. Optimum conditions namely initial pH (2-12), initial IC dye concentration (10-50 mg/L), agitation rate (120 rpm), contact time (0-45 h), adsorbent dosage (0.01-0.20 g) for the adsorption process were determined. The adsorption of IC dye was studied using the adsorption method, and the q(m) value was calculated as 697.82 mg/g at 298 K from a non-linear Sips isotherm. Adsorption kinetics showed that the adsorption process followed a pseudo-second-order kinetic. Error functions were also calculated to assess the validity and applicability of the isotherm and kinetic models and the reproducibility of the results. Negative enthalpy and Gibbs free energy indicated that the adsorption process was exothermic and spontaneous. FTIR-ATR studies revealed that IC adsorption occurred mainly via electrostatic interactions and pi-pi interactions. The performance of PLA/PANI/20 composite in distilled water, drinking water and tap water samples was evaluated and determined as 96.7%, 91.5%, and 87.1%, respectively. The reusability experiments were conducted. After reusability experiments, the adsorption percentage was changed from 96.51% to 71.23% after 5th cycle. All the results showed that PLA/PANI composites can be used as a potential and effective adsorbent for the removal of anionic pollutants from wastewater and different water samples.
Keywords: adsorption; indigo carmine; poly(lactic acid); polyaniline; EQUILIBRIUM; ADSORBENT; CAPACITY; KINETICS; ISOTHERM; CARBON; ACID); Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology